From novice to expert: Trajectories of skill acquisition through work - Lintzeris, Paraskevas (Adult Education Critical Issues, 2021)
Work is, by its very nature, its spatio-temporal function and its role in social life, a field of human interaction. As such is a constant source of experiences that evolutionarily and sometimes transformatively affect the body of knowledge, skills and competences that each individual possesses and activates during the practice of his/her profession. The paper examines three theories regarding the ways in which professional / vocational skills are acquired through work aiming to succeed the transition from the state of the novice to that of the expert: the theory of S.E. Dreyfus & H.L. Dreyfus, the analysis of Richard Sennett and the approach of Chris Argyris and Donald Schön. The importance of working experience and in particular problem solving is emphasized in order the learner to have a subjective acquisition, internalization and consolidation of theoretical knowledge. At the same time, the importance of theoretical, scientific knowledge for the understanding, control and generalization of practical experience is underlined.